A Re-Evaluation of J.C. Bach's Cello Concerto in C Minor (W. C11) in the Context of Galant Aesthetics for Soloist Practice - Ikram, Muhammad; Sina, Ibnu; Dary, Mohammad; Anggraini, Nora (Scoring: Journal of Film Music, 2025)
Johann Christian Bach's (1735–1782) Cello Concerto in C Minor (W. C11) represents a unique intersection of eighteenth-century European musical traditions. This work, likely composed for the London concert market but infused with Mannheimian influences, serves as an ideal case study for investigating the transfer of style and solo performance practices in the Galant period. This article re-evaluates the concerto through a three-dimensional analysis: (1) a textual and comparative analysis of the primary manuscript source (British Library Add MS 31723) and a problematic modern edition; (2) a placement of the work within the biographical and social context of J.C. Bach's London career, as well as the resonance of the Mannheimian idiom in his orchestration; and (3) an investigation of the technical and interpretative implications for modern solo cellists seeking to reconstruct a historically appropriate approach. The findings reveal that this concerto is not simply a transitional work, but rather a mature expression of the Galant aesthetic, in which Mannheimian dramatic elements (Steigerung, Raketen) are harnessed to enhance the lyrical and dialogic expression of the solo cello. This study concludes that a stylistically authentic performance requires a rejection of the romanticization in Paul Müller's standard edition (1936) and the adoption of principles of articulation, ornamentation, and rhetoric drawn from contemporary sources, thus restoring the work's position as an important touchstone in the early Classical cello repertoire.